2002
DOI: 10.1080/01446190110101218
|View full text |Cite
|
Sign up to set email alerts
|

Construction related factors influencing the choice of concrete floor systems

Abstract: Designers have a wide choice of concrete floor systems for their buildings. They can choose from three basic types available: in situ, precast or hybrid construction. A survey was conducted within the UK construction industry to investigate, in particular, the construction related factors influencing the choice of concrete floor systems. The data collected were subjected to frequency and severity index analyses, Kendall's concordance test and the chi-squared tests to produce a rank ordering of 12 construction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 5 publications
0
63
0
Order By: Relevance
“…This means that the respondents are familiar with cast in situ and pre cast/ prefabrication method while in the case of semi precast method, they are not familiar with the method. The findings correspond with Idrus andNewman, (2002) andSeeley, (1995) in terms of their classification of solid slab construction. They classified solid slab construction in majorly cast in situ and precast while semi precast was out of their classifications.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…This means that the respondents are familiar with cast in situ and pre cast/ prefabrication method while in the case of semi precast method, they are not familiar with the method. The findings correspond with Idrus andNewman, (2002) andSeeley, (1995) in terms of their classification of solid slab construction. They classified solid slab construction in majorly cast in situ and precast while semi precast was out of their classifications.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…One is explained in the important research of Warszawski [14], who found six main criteria: architectural design, physical performance, technology, management, economics, and marketing. Other researchers have also reported criteria for selecting building systems for such things as concrete floors [15], roofs [16], industrialized housing [17,18], and building automation [19].…”
Section: Methodsmentioning
confidence: 99%
“…The relative significance ranking (RSI) was used for ranking of the factors studied. These methods have been used in construction research by authors such as, [14], [15], [16], [17], [18] among others.…”
Section: Methodsmentioning
confidence: 99%